The Codes of Mental Transformation in Education: A Thematic Analysis of Graduate Social Studies Students’ Perspectives on Artificial Intelligence. - Büyükboyacı, Şengül; Yozçu, Ömer (Electronic Turkish Studies, 2026)
This study examines the perceptions, evaluations, and professional expectations of postgraduate Social Studies teacher candidates regarding artificial intelligence (AI) and its role in education. Adopting a qualitative research approach, the study was designed as a case study. Data were collected through semistructured interviews conducted with six graduate students enrolled in the Social Studies Education programme at Süleyman Demirel University during the 2024–2025 academic year. The collected data were analysed using content analysis, through which codes, categories, and themes were identified. The findings reveal that participants predominantly conceptualise AI as a technological tool or application, yet their levels of conceptual awareness vary considerably. While AI is viewed as a supportive instrument for teachers—particularly in lesson preparation, material design, individualised learning, and time management— it is not regarded as capable of replacing the teacher. Empathy, guidance, and classroom management are emphasised as irreplaceable human dimensions of the teaching profession. Participants also noted that AI can enrich Social Studies teaching by facilitating the visualisation of historical events, producing digital materials, and supporting the interpretation of maps and graphs. However, concerns were expressed about ethical issues, data security, and cognitive dependency. Based on these findings, the study suggests that teacher education programmes could integrate AI literacy into the curriculum and develop digital pedagogy modules that enhance ethical awareness, critical thinking, and creative technology use. Practical AI workshops and interdisciplinary simulation-based learning environments could also be introduced to strengthen candidates’ technological and pedagogical competencies. Additionally, universities may establish AI application centres where prospective teachers can experiment with digital tools, share experiences, and collaborate across disciplines. The study concludes that teacher candidates can be supported in developing AI literacy, ethical awareness, and digital creativity so that AI functions as a collaborative rather than competitive force in education.